Use of CBCT plus plan robustness for reducing QACT frequency in intensity‐modulated proton therapy: Head‐and‐neck cases. Issue 11 (15th August 2022) - Yao, Weiguang; Zhang, Baoshe; Han, Dong; Polf, Jerimy; Vedam, Sastry; Lasio, Giovanni; Yi, Byongyong
Abstract: Purpose: Anatomic variation has a significant dosimetric impact in intensity‐modulated proton therapy. Weekly or biweekly computed tomography (CT) scans, called quality assurance CTs (QACTs), are used to monitor anatomic and resultant dose changes to determine whether adaptive plans are needed. Frequent CT scans result in unwanted QACT dose and increased clinical workloads. This study proposed utilizing patient setup cone‐beam CTs (CBCTs) and treatment plan robustness to reduce the frequency of QACTs. Methods: We retrospectively analyzed data from 27 patients with head‐and‐neck cancer, including 594 CBCTs, 136 QACTs, and 19 adaptive plans. For each CBCT, water‐equivalent thickness (WET) along the pencil‐beam path was calculated. For each treatment plan, the WET of the first‐day CBCT was used as the reference, and the mean WET changes (ΔWET) in each following CBCT was used as the surrogate of proton range change. Using CBCTs acquired prior to a QACT, we predicted the ΔWET on the QACT day by a linear regression model. The impact of range change on target dose was calculated as the predicted ΔWET weighted by the monitor units of each field. In addition, plan robustness was estimated from the robust dose‐volume histograms (DVHs) and combined with ΔWET to reduce QACT frequency. Robustness was estimated from the distance between the DVH curves of the nominal and worst scenarios. Results: When the estimated mean ΔWET was <6.5 mm (or <7.5 mm if the robustness was >95%), the QACT could be skipped without missing any adaptive planning; otherwise a QACT was required. Overall, 41% of QACTs could be eliminated when ΔWET was <6.5 mm and 56% when ΔWET was <7.5 mm, and robustness was >95%. At least one QACT could have been omitted in 25 of the 27 cases under skipping thresholds at ΔWETs <7.5 mm and R > 95%. Conclusion: This study suggests that the number of QACTs can be greatly reduced by calculating range change in patient setup CBCTs and can be further reduced by combining this information with analyses of plan robustness.